P146 Golimumab in rheumatoid and psoriatic arthritis. The relationship between minimum serum concentration, anti-golimumab antibodies and activity of disease. (March 2019) - Uceda, J; Fobelo, MJ; Hernandez, R
Abstract : Career situation of first and presenting author: Young investigator. Introduction: Currently there is very little information on optimal levels of golimumab in patients with polyarthritis. Objectives: The main objective was to analyze the minimal serum concentration of golimumab (GOL), anti-golimumab antibodies (AcGOL) and its relation to the activity of the disease measured by DAS 28 index, in rheumatoid arthritis (RA) and psoriatic arthritis (PA). Methods: We conducted a retrospective observational study with RA or PA patients on golimumab treatment between 2011 and 2016. We analized the age, sex, diagnosis, dose, dose interval, duration of treatment, concomitant disease modifying drugs (DMARs), minimum concentration of GOL (GOL Cmin), AcGOL and DAS28 levels. Sampling was performed on the day corresponding to the dose of golimumab, prior to administration, in order to obtain the minimum levels of the drug. The analytical technique used for the determination was the Promonitor® sandwich ELISA. Results: 10 RA, 5 AP patients were selected. Median age 53 years. 67% women. All with golimumab 50 mg with an administration interval of 28 to 41 days. Duration of treatment 16.73 months (median). 80% underwent combination therapy with DMARDs. Only one patient (RA) presented levels of AcGOL, with undetectable Cmin, DAS28 of 4.05. Golimumab levels in patients without AcGOL and DAS28 <3.2: 1 Cmin <0.25 mcg/mL, 5 Cmin 0.26–0.5 mcg/mL, 1 Cmin 0.5–1.4 mcg/mL and 1 2mcg/mL Cmin. In patients with DAS28 >3.2 were: 2 Cmin <0.25 mcg/mL, 2 Cmin 0.26–0.5 mcg/mL, 2 Cmin 0.5–1.4 mcg/mL and 1 Cmin of 2.2 mcg/mL. Conclusions: Very variable GOL Cmin values (<0.25–2.2 mcg/mL) were obtained. 80% with DAS28 <3.2 had a GOL Cm: 0.26–0.5 mcg/mL. Because of the limited information currently available on the optimal range of golimumab levels, further studies are needed to evaluate the relationship between serum drug levels and patient disease activity data. Disclosure of Interest: None declared.